International Negotiations in Multinational Company of IUY. - Kolesnik, Nikolaj; Pichanič, Mikuláš, 1942-; Říha, David; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2015)
Negotiation has been a frequent subject of research over past centuries, especially in 20. century this area of business has been recognizing an increasing popularity. This thesis is exploring connections between employees' behaviour of the International Union of Youth in Prague and their negotiation style. Pursuant the research it appears that we can predict employees negotiation style if we are familiar with their behaviour. Moreover, findings showed that there are positive and negative correlations between style of negotiation and behaviour of employees.
Vedoucí práce: Mikuláš Pichanič
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses